MEMBANGUN POLITIK HUKUM INDONESIA BERCORAK RESPONSIF PERSPEKTIF IUS CONSTITUENDUM - Sodiq, Nur (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 5 No 2 (2016)DO - 10.24843/JMHU.2016.v05.i02.p02, 2016)
Legal establishment of a joint legislative task of the executive. Law concretely manifest in a legislation. The times are always accompanied by a society is demands, which is in line with the progress of the development of science and technology globally. Functions of the state in charge of all the rules to organize and meet the needs of its citizens is done throught legal political policy. The law requires the develoment of a progressive politics that is always dynamic. Resonsibility society must be accomodated in e lagislation. Shades of the Indonesian legal system of formal legalistif formal positiviestic character is not aspirational again in the resolution of lawsuits that are very dynamic and responsive at this time, for the next legislators and executive branches in the establishment of the rule of law it is time to shift the mindset forwards the type of legal realistic, practical and progressive. Guidelines used by the legislators it was time to adopt, replicate and wear character types law the families of law outside continental Europe, one of which types and styles of breath common law system. All toward political reform law is realized through the establishment of policies that must be taken for the ralization of the type of welfare state. Pembentukan hukum merupakan tugas legislatif bersama eksekutif. Hukum secara konkrit dirumuskan dalam suatu perundang-undangan. Perkembangan hukum selalu diiringi oleh berbagai tuntutan kebutuhan masyarakat, yang seiring dan sejalan dengan kemajuan perkembangan ilmu pengetahuan dan teknologi baik secara nasional maupun global. Fungsi negara dalam mengisi segala aturan untuk menyelenggarakan dan memenuhi kebutuhan hidup warganya dilakukan melalui kebijakan politik hukumnya. Pembangunan politik hukum memerlukan progresivitas yang dinamis. Responsivitas kebutuhan masyarakat mesti dapat tertampung dan diakomodir dalam suatu peraturan perundang-undangan. Corak sistem hukum Indonesia yang berwatak positivistik legalistik formal sudah tidak aspiratif lagi dalam penyelesaian tuntutan hukum yang sangat dinamis dan responsif saat ini. Dengan demikian ke depan diharapkan para legislatif dan eksekutif dalam pembentukan norma hukum sudah saatnya menggeser pola pikir ke arah tipe hukum realistis, praktis dan progresif. Pedoman yang dipakai dalam membentuk undang-undang sudah saatnya mengadopsi, maupun meniru dan memakai tipe-tipe karakter hukum keluarga diluar hukum Eropa kontinental, salah satunya tipe dan corak nafas hukum common law system. Semua arah pembangunan pembentukan hukum diwujudkan melalui kebijakan yang mesti diambil demi terwujudnya tipe negara kesejahteraan.
Keywords: Legal Politics, Responsive, Next Time, Politik Hukum, Responsif, Masa Kedepan